KEPEMIMPINAN FX.HADI RUDYATMO DALAM MEWUJUDKAN SOLO KOTA LAYAK ANAK - Yunita Ratna Sari (Program Magister Ilmu Politik, Universitas Diponegoro, 2017)
Solo is one of the two Cities in Indonesia that received the highest award of District / City Worthy Children's implementation from President JokowiWidodo as the City of Eligible Children. The success of Solo to get the award of Decent Child's City can not be separated from the leadership FX.HadiRudyatmo as the Mayor of Solo. The objectives of this research are: (1) To know and explain the leadership of FX.HadiRudyatmo in realizing the Solo of Decent City, (2) To analyze and analyze the factors that make Solo Municipal Children's Favorite and (3) to know and analyze the actors who contribute greatly in Solo Kota Decent Children. The method used in this study is a qualitative descriptive approach that explains the results of research, assessment and other references reinforced by empirical data conducted through interviews and observation. The results showed that the leadership of FX.HadiRudyatmo in realizing the Decent City Solo is very democratic but the egosektoral among the Organization of Regional Devices in realizing the Solo Municipal Decent Children is still high and there are still problems that can not be resolved even though Solo gets the predicate Solo Kota Major Main is the number of children who exposed to HIV / AIDS is still high and the availability of child data information management system. Recommendations given to the Government are to build more intense communications and improve routine coordination among the Regional Device Organizations through scheduled meetings amongst the WTO, promoting socialization and education to all levels of society on HIV / AIDS as well as the creation of a web data base on child data.Keywords: Leadership, Head of Region, District / City Eligible Children